Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.1101
|View full text |Cite
|
Sign up to set email alerts
|

AB0654 An ultrasound assessment of the hand and wrist in egyptian patients with systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc, scleroderma) is a systemic disease characterized by fibrosis, progressive vascular obliteration and the production of autoantibodies.Ultrasound (US) imaging has advantages of simplicity, low cost, noninvasiveness, real-time capability and portability compared with traditional EDX. US imaging also offers high temporal and spatial resolutions, and can potentially provide dynamic anatomical information regarding local structures and kinesiology, few studies evaluate joint and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several different treatment approaches and strategies for SSc-ILD have recently been published [2,66,67]. Our SLR showed that immunosuppressive therapies are the current standard of care in the treatment of SSc-ILD.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several different treatment approaches and strategies for SSc-ILD have recently been published [2,66,67]. Our SLR showed that immunosuppressive therapies are the current standard of care in the treatment of SSc-ILD.…”
Section: Discussionmentioning
confidence: 80%
“…The efficacy of treatments in SSc-ILD have been reviewed in detail elsewhere [2,66]. Non-pharmacological treatments and management strategies may have a role in supporting patients with SSc-ILD such as supplemental oxygen, pulmonary rehabilitation, physical activity and encouraging smoking cessation [66,78], but were not evaluated in this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various parts of the world show that the practice of ozone therapy seems to be effective, safe, and low risk as an adjunct therapy in the treatment of lower-limb ulcers, whether applied topically through water, oil, or gas; subcutaneously (perilesional); systemically (rectally, intravenously); and/or in combination 6–13 …”
Section: Resultsmentioning
confidence: 99%
“…Further, the gas potentially acts to trigger controlled oxidative stress when administered in precise therapeutic doses. Studies indicate that there is a significant benefit to healing using this therapy, and this has encouraged its application in a number of different ways 6–13 …”
Section: Introductionmentioning
confidence: 99%